2012
DOI: 10.1007/s10903-012-9717-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes and Metabolic Syndrome in a Migrant Mixtec Population, Baja California, Mexico

Abstract: This study was conducted to determine the prevalence and correlates of metabolic syndrome (MS) and diabetes among a migrant Mixtec population residing in San Quintin, Baja California, Mexico. A cross-sectional study utilizing data collected during a 2-day clinic in 2008 in a rural farming community with a high prevalence of Mixtec Indians. Interviews and clinical examinations were performed to assess sociodemographic data, medical history and anthropometric measures. Blood samples were obtained to measure glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Apart from obesity, smoking and lack of physical exercise are also associated with an exaggerated increase in plasma triglycerides upon excessive alcohol consumption [20 & ]. The inconclusive results between alcohol consumption and the metabolic syndrome may be explained by differential effects of alcohol on the different components of the metabolic syndrome [38,39]. The inconclusive results between alcohol consumption and the metabolic syndrome may be explained by differential effects of alcohol on the different components of the metabolic syndrome [38,39].…”
Section: Interaction Between Lifestyle Alcohol and Plasma Triglyceridesmentioning
confidence: 99%
“…Apart from obesity, smoking and lack of physical exercise are also associated with an exaggerated increase in plasma triglycerides upon excessive alcohol consumption [20 & ]. The inconclusive results between alcohol consumption and the metabolic syndrome may be explained by differential effects of alcohol on the different components of the metabolic syndrome [38,39]. The inconclusive results between alcohol consumption and the metabolic syndrome may be explained by differential effects of alcohol on the different components of the metabolic syndrome [38,39].…”
Section: Interaction Between Lifestyle Alcohol and Plasma Triglyceridesmentioning
confidence: 99%
“…MetS has become a global public health issue. Its prevalence has been estimated to vary between 20–27% in adults from developing countries [ 7 , 8 , 9 , 10 ], and even higher in developed nations [ 11 , 12 , 13 ]. According to the National Health and Nutrition Examination Survey in the U.S., the overall prevalence of MetS increased from 32.9% in 2003–2004 to 34.7% in 2011–2012 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found a prevalence of Type 2 DM among indigenous groups in neighboring Southern Mexican states of 8.7% among Zapotec and 6.9% among Mixe groups [16]. Data from a 2008 study in a migrant Mixtec population in rural Northwestern Mexico, found the prevalence of MetS was 41.1%, while that of Type 2 DM was 26.2% [17].…”
Section: Introductionmentioning
confidence: 99%